A fireproof and heat-insulating integrated composite structure

By adopting the composite composite structure of fire and heat insulation on the surface of the aircraft, the combination of expansion fireproof coatings, metal titanium foil, gas gel felt and phase transformer material is used to solve the poor thermal insulation performance of the existing thermal protection structure and insufficient long -term stability. The problem has achieved efficient thermal protection performance and light -quality design.

CN118683152BActive Publication Date: 2025-01-24SOUTHWEST TECHNICAL ENGINEERING RESEARCH INSTITUTE OF CHINA SOUTH IND GROUP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411150634.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-01-24
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

The thermal protection structure on the surface of existing aircraft has problems such as poor thermal insulation performance, poor long-term stability, large ablation reversal, and overweight, which cannot meet the thermal protection needs of missiles and other aircraft.

Method used

A composite composite structure of fire prevention and heat insulation, including fire prevention layers, transition, first protection layer, first protective layer, first heat insulation layer, secondary insulation layer and second protection layer, through expansion fireproof coatings, metal titanium foil,, metal titanium foil,, metal titanium foil, and The combination of gas gel felt and phase -changing materials can achieve the purpose of insulation and fire prevention.

Benefits of technology

The composite structure has the advantages of good thermal insulation, light weight, thin thickness, long -term stability, and easy installation. It can effectively improve the thermal protection performance of the aircraft, and it is suitable for the high temperature environment of 800 to 1200 ° C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118683152B_ABST
    Figure CN118683152B_ABST
Patent Text Reader

Abstract

The present invention provides a fireproof and heat-insulating integrated composite structure, which relates to the field of fireproof and heat-insulating structures, and comprises a fireproof layer (10), a transition layer (20), a first protective layer (30), a first heat-insulating layer (40), a second heat-insulating layer (50) and a second protective layer (60) in sequence; wherein the fireproof layer (10) adopts an intumescent fire-retardant coating, the transition layer (20) adopts a primer, the first protective layer (30) and the second protective layer (60) adopt metal titanium foil, the first heat-insulating layer (40) adopts an aerogel felt, and the second heat-insulating layer (50) adopts a phase change material. The composite structure has the advantages of good heat-insulating and fire-proof performance, light weight, thin thickness, good long-term stability, and easy installation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fireproof and heat-insulating structures, and in particular to a fireproof and heat-insulating integrated composite structure. Background Art

[0002] During high-speed flight, missiles and other aircraft are subjected to large amounts of aerodynamic heating on their outer surfaces, resulting in high surface temperatures, which in turn reduces the stiffness and strength of the aircraft surface, and is accompanied by problems such as thermal stress and thermal strain, which reduces the bearing capacity of the aircraft's outer surface. At the same time, long-term high-temperature environments can cause the temperature inside the aircraft cabin to rise, affecting the stability of the internal structure (e.g., missile charges, etc.). In addition, the superposition of thermal stress and the aircraft's aerodynamic load will further affect the stability of the structure, causing the aircraft structure to deform excessively under the dual effects of thermal stress and aerodynamic force, affecting its flight reliability. Therefore, during the design process, a heat-insulating structure is usually set on the surface of the aircraft to achieve the purpose of thermal protection during high-speed flight, and also to ensure the safety of the aircraft against accidental fire and high-temperature environments during storage and transportation.

[0003] At present, the thermal protection of aircraft surfaces is mainly achieved by fiber felt coating and protective coating spraying. The coated fiber felt has poor thermal insulation performance, poor long-term stability, large ablation retreat, and overweight under long-term high temperature, and cannot meet the thermal protection needs of missiles and other aircraft. The sprayed protective coating has problems such as smoke, slag, cracking, and low bonding strength. The coating loses its own protective effect after defects occur, and it is easy to cause the aircraft surface to be directly exposed to high temperature environments. Therefore, the research and development of a protective structure that has both thermal insulation and fire protection functions, light weight, thin thickness, and good long-term stability has great practical application value in the aerospace field. Summary of the invention

[0004] In view of the problems existing in the above prior art, the purpose of the present invention is to provide a fireproof and heat-insulating integrated composite structure, which has the advantages of good heat insulation and fireproof performance, light weight, thin thickness, good long-term stability, and easy installation.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A fireproof and heat-insulating integrated composite structure comprises a fireproof layer, a transition layer, a first protective layer, a first heat-insulating layer, a second heat-insulating layer and a second protective layer in sequence; wherein the fireproof layer adopts an intumescent fire-retardant coating, the transition layer adopts a primer, the first protective layer and the second protective layer adopt metal titanium foil, the first heat-insulating layer adopts aerogel felt, and the second heat-insulating layer adopts a phase change material.

[0007] Based on further optimization of the above scheme, the thickness of the fireproof layer is 0.6-1.0 mm; the intumescent fire retardant coating includes a film-forming material, a flame retardant and a functional filler, wherein the mass ratio of the film-forming material, the flame retardant and the functional filler is 2-3:6-10:1-3.

[0008] Based on further optimization of the above scheme, the film-forming material is a high-elastic polyurethane polymer (wherein the high-elastic polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 5-8:4-7:2-4; the functional filler is composed of nano-grade aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres, and the mass ratio between them is 5-10:2-5:3-8.

[0009] Based on further optimization of the above scheme, the particle size of the ultrafine ceramic hollow microspheres is 20-50 μm, and the melting point is not less than 1600° C.

[0010] The flame retardant composed of ammonium polyphosphate, pentaerythritol and melamine is combined with a film-forming material to expand and carbonize in a high-temperature environment to form a dense carbonized layer, thereby achieving the purpose of heat insulation and fire prevention; at the same time, functional fillers composed of nano-aluminum hydroxide, expanded graphite and ultra-fine ceramic hollow microspheres are used to, firstly, use nano-aluminum hydroxide to inhibit the amount of smoke and reduce material loss during the high-temperature carbonization process, secondly, enhance the strength of the carbonized layer through nano-aluminum hydroxide, and thirdly, fill the gaps in the expanded carbonized layer through expanded graphite and ultra-fine ceramic hollow microspheres, thereby enhancing the heat insulation performance of the carbonized layer.

[0011] Based on further optimization of the above solution, the transition layer uses epoxy primer, and the thickness of the transition layer is 40 to 60 μm; the bonding strength between the fireproof layer and the first protective layer is improved by the transition layer.

[0012] Based on further optimization of the above solution, the thickness of the first protective layer (when the first protective layer is flat) is 0.03-0.1 mm; the first protective layer adopts a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure.

[0013] Based on the further optimization of the above scheme, the shape of the protrusion is any one of rice grain, pearl and water drop; the diameter of the protrusion is 1-2.5 mm, the height is 0.4-1.0 mm; the distance between two adjacent protrusions is 4-8 mm; the number of protrusions per unit area in the first protective layer is 1.5x10 4 ~6x10 4 indivual.

[0014] The protrusions of the first protective layer are arranged to improve the rigidity of the first protective layer through the strain hardening effect produced during the pressing process of the protrusions; the roughness of the transition layer corresponding to the first protective layer is increased through the distribution of the protrusions, and the interface bonding force between the first protective layer and the fireproof layer is increased by using the transition layer; the wrinkles formed during the molding process of the protective layer are reduced through the preparation of the protrusions, thereby reducing the weak points of failure, avoiding damage to the protective layer, and improving the overall liquid penetration resistance of the composite structure; the protrusions provide a buffer gap for the fireproof layer to ensure that the fireproof layer completes expansion and carbonization while avoiding the expansion of the fireproof layer. The first is to prevent cracking, falling off and other problems caused by impact force; the second is to convert the reflective surface from mirror reflection to dot matrix diffuse reflection through uneven protrusions, thereby expanding the heat reflection area and improving the reflection efficiency; the third is to utilize the continuous uneven protrusions to cooperate with the first thermal insulation layer to form a plurality of cavity matrices, thereby changing the interlayer flow field and forming micro air gaps, effectively blocking heat conduction, inhibiting heat convection, and improving the thermal insulation effect; the fourth is to achieve point contact between the first protective layer and the first thermal insulation layer, thereby reducing heat conduction between the first protective layer and the first thermal insulation layer, so that the heat is effectively dissipated in the cavity matrix, further improving the thermal insulation effect.

[0015] Based on further optimization of the above scheme, the first thermal insulation layer adopts basalt fiber reinforced silica aerogel felt, and the thickness of the first thermal insulation layer is 2 to 5 mm; wherein, the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.78 to 1, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.017 to 0.020 W / (m•K).

[0016] Using small-diameter basalt fibers as reinforcing fibers for nanoporous silica aerogel can effectively limit the solid heat conduction of the fibers themselves, making the basalt fiber felt itself have a lower thermal conductivity. At the same time, using short-diameter basalt fibers to form a low-density preform can further reduce the density of the fiber-reinforced aerogel composite while ensuring its mechanical properties. The diameter of the fiber preform is close to the wavelength of near-infrared radiation, which can produce a strong diffraction and scattering effect on the near-infrared radiation, thereby further enhancing the high-temperature infrared radiation heat conduction barrier effect. In addition, the addition of basalt fibers can effectively solve the problems of pure aerogel being brittle and easy to break.

[0017] Based on the further optimization of the above scheme, the volume density of the basalt fiber reinforced silica aerogel felt is 150-170 kg / m 3 The bulk density of the preform formed by basalt fiber is 80~90kg / m 3 The density of silica aerogel is 70~80kg / m 3 .

[0018] Based on the further optimization of the above scheme, the thickness of the second thermal insulation layer is 2-5 mm; the phase change material is composited by a phase change raw material and a matrix material, the phase change raw material is a microcapsule, the particle size of the microcapsule is 10-100 μm, wherein the encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea (through the combination of urea and a specific formula, the formaldehyde residue is effectively reduced to avoid affecting the coating performance of the encapsulation material), the phase change core of the microcapsule is paraffin; the matrix material is epoxy resin; the phase change temperature of the phase change material is 95-120 ° C, and the density is 1.0-1.3 g / cm 3 , phase change enthalpy value is 220~260J / g.

[0019] Based on further optimization of the above scheme, the mass ratio between the epoxy resin (matrix material) and the microcapsule (phase change raw material) is 1:1-15; the mass ratio between the encapsulation material of the microcapsule (i.e., melamine formaldehyde resin) and paraffin is 6:1; the mass ratio of melamine and formaldehyde urea in the encapsulation material is 10:20-30:1-5.

[0020] Based on further optimization of the above solution, the thickness of the second protective layer is 0.03-0.1 mm, and the second protective layer is a flat and smooth metal titanium foil, which facilitates the installation of the second protective layer.

[0021] The following are the effects of the technical solution of the present invention:

[0022] The present application forms a dense insulation layer through the cooperation of the fireproof layer, the transition layer, the first protective layer, the first heat-insulating layer, the second heat-insulating layer and the second protective layer, and realizes the isolation of flame and heat transfer through the expansion and carbonization of the fireproof layer when it encounters heat, and completes the close and stable combination between the fireproof layer and the first protective layer through the transition layer. The cooperation between the first protective layer, the fireproof layer and the first heat-insulating layer not only improves the heat reflection efficiency and the heat barrier effect, but also provides a buffer for the fireproof layer that expands and carbonizes when it encounters heat, and avoids the problems of interlayer separation and cracks in the composite structure during the carbonization process. And synergistically improve the fireproof and heat-insulating effects of the entire composite structure; at the same time, a large amount of heat is absorbed through the phase change of the second insulation layer to achieve effective thermal protection, and the overall thermal insulation performance of the composite structure is further improved while ensuring that the composite structure is light and thin; in addition, the present application combines the second protective layer with the first protective layer, which not only realizes the protection of the first insulation layer and the second insulation layer, but also avoids damage and separation of the first insulation layer and the second insulation layer during the thermal protection process, and further improves the overall reflection and blocking of the composite structure to heat, and improves the fireproof and heat-insulating effects.

[0023] The composite structure of the present application has a simple overall structure, has fireproof and heat-insulating functions, is thin, light, and easy to install. It is suitable for fireproof and heat-insulating hot-end components of various equipment in a high temperature environment of 800 to 1200°C, has a wide range of applications, and has good insulation effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the overall composite structure in an embodiment of the present invention.

[0025] Figure 2 Schematic diagram of the structure of the first protective layer of the composite structure in an embodiment of the present invention.

[0026] Among them, 10, fireproof layer; 20, transition layer; 30, first protective layer; 40, first thermal insulation layer; 50, second thermal insulation layer; 60, second protective layer. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0028] Embodiment 1:

[0029] A fireproof and heat-insulating integrated composite structure, such as Figure 1 As shown: it includes a fireproof layer 10, a transition layer 20, a first protective layer 30, a first heat-insulating layer 40, a second heat-insulating layer 50 and a second protective layer 60 in sequence; wherein the thickness of the fireproof layer 10 is 0.6 mm, and the fireproof layer 10 adopts an intumescent fire-retardant coating, and the intumescent fire-retardant coating includes a film-forming material, a flame retardant and a functional filler, wherein the mass ratio of the film-forming material, the flame retardant and the functional filler is 2:6:1; the film-forming material is a high-elasticity polyurethane polymer (wherein the high-elasticity polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 5:4:2; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 20μm, and the melting point is not less than 1600℃), and the mass ratio between them is 5:2:3.

[0030] The transition layer 20 is made of epoxy primer, and the thickness of the transition layer 20 is 40 μm. The transition layer 20 is used to enhance the bonding strength between the fireproof layer 10 and the first protective layer 30 .

[0031] The thickness of the first protective layer 30 (when the first protective layer 30 is flat) is 0.03 mm. The first protective layer 30 adopts a metal embossed titanium foil structure, that is, protrusions (such as Figure 2 As shown, to ensure the multiple effects of the first protective layer 30, the protrusions are oriented toward the transition layer 20). The shape of the protrusions is rice grain-like; the diameter of the protrusions is 1 mm and the height is 0.4 mm; the distance between two adjacent protrusions is 4 mm; the number of protrusions per unit area in the first protective layer 30 is 6x10 4 indivual.

[0032] The first thermal insulation layer 40 is made of basalt fiber reinforced silica aerogel felt, and the thickness of the first thermal insulation layer 40 is 2 mm; wherein the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.78, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.020 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 159.74 kg / m 3 The bulk density of the preform formed by basalt fiber is 89.74kg / m 3 The density of silica aerogel is 70kg / m 3 .

[0033] The thickness of the second thermal insulation layer 50 is 2 mm. The second thermal insulation layer 50 adopts phase change material, which is composed of a phase change raw material and a matrix material. The phase change raw material is a microcapsule, and the average particle size of the microcapsule is 30 μm. The encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:20:1. The phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e., melamine formaldehyde resin) and the paraffin is 6:1. The matrix material is epoxy resin, and the mass ratio between epoxy resin (matrix material) and microcapsule (phase change raw material) is 1:2. The phase change temperature of the phase change material is 95°C, and the density is 1.0 g / cm 3 , phase change enthalpy is 220J / g.

[0034] The thickness of the second protective layer 60 is 0.03 mm. The second protective layer 60 is a flat and smooth metal titanium foil, which facilitates the installation of the second protective layer 60 .

[0035] Embodiment 2:

[0036] A fireproof and heat-insulating integrated composite structure, such as Figure 1As shown: it includes a fireproof layer 10, a transition layer 20, a first protective layer 30, a first heat-insulating layer 40, a second heat-insulating layer 50 and a second protective layer 60 in sequence; wherein the thickness of the fireproof layer 10 is 0.8 mm, and the fireproof layer 10 adopts an intumescent fire-retardant coating, and the intumescent fire-retardant coating includes a film-forming material, a flame retardant and a functional filler, wherein the mass ratio of the film-forming material, the flame retardant and the functional filler is 2.5:8:2; the film-forming material is a high-elasticity polyurethane polymer (wherein the high-elasticity polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 6:5:3; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 35μm, and the melting point is not less than 1600℃), and the mass ratio between them is 8:3:5.

[0037] The transition layer 20 is made of epoxy primer, and the thickness of the transition layer 20 is 50 μm. The transition layer 20 is used to enhance the bonding strength between the fireproof layer 10 and the first protective layer 30 .

[0038] The thickness of the first protective layer 30 (when the first protective layer 30 is flat) is 0.06 mm. The first protective layer 30 adopts a metal embossed titanium foil structure, that is, protrusions (such as Figure 2 As shown, to ensure the multiple effects of the first protective layer 30, the protrusions are oriented toward the transition layer 20). The protrusions are pearl-shaped; the diameter of the protrusions is 1.5 mm and the height is 0.7 mm; the distance between two adjacent protrusions is 6 mm; the number of protrusions per unit area in the first protective layer 30 is 3.5x10 4 indivual.

[0039] The first thermal insulation layer 40 is made of basalt fiber reinforced silica aerogel felt, and the thickness of the first thermal insulation layer 40 is 3 mm; wherein, the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.85, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.018 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 163.24 kg / m 3 The bulk density of the preform formed by basalt fiber is 88.24kg / m 3 The density of silica aerogel is 75kg / m 3 .

[0040] The thickness of the second thermal insulation layer 50 is 3 mm. The second thermal insulation layer 50 adopts phase change material, which is composed of a phase change raw material and a matrix material. The phase change raw material is a microcapsule, and the average particle size of the microcapsule is 60 μm. The encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:25:3. The phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e., melamine formaldehyde resin) and the paraffin is 6:1. The matrix material is epoxy resin, and the mass ratio between epoxy resin (matrix material) and microcapsule (phase change raw material) is 1:6. The phase change temperature of the phase change material is 110°C, and the density is 1.2 g / cm 3 , phase change enthalpy is 240J / g.

[0041] The thickness of the second protective layer 60 is 0.06 mm. The second protective layer 60 is a flat and smooth metal titanium foil, which facilitates the installation of the second protective layer 60 .

[0042] Embodiment 3:

[0043] A fireproof and heat-insulating integrated composite structure, such as Figure 1 As shown: it includes a fireproof layer 10, a transition layer 20, a first protective layer 30, a first heat-insulating layer 40, a second heat-insulating layer 50 and a second protective layer 60 in sequence; wherein the thickness of the fireproof layer 10 is 1.0 mm, and the fireproof layer 10 adopts an intumescent fire-retardant coating, and the intumescent fire-retardant coating includes a film-forming material, a flame retardant and a functional filler, wherein the mass ratio of the film-forming material, the flame retardant and the functional filler is 3:10:3; the film-forming material is a high-elasticity polyurethane polymer (wherein the high-elasticity polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio thereof is 8:7:4; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 50 μm, and the melting point is not less than 1600° C.), and the mass ratio thereof is 10:5:8.

[0044] The transition layer 20 is made of epoxy primer, and the thickness of the transition layer 20 is 60 μm. The transition layer 20 is used to enhance the bonding strength between the fireproof layer 10 and the first protective layer 30 .

[0045] The thickness of the first protective layer 30 (when the first protective layer 30 is flat) is 0.1 mm. The first protective layer 30 adopts a metal embossed titanium foil structure, that is, protrusions (such as Figure 2As shown, to ensure the multiple effects of the first protective layer 30, the protrusions are oriented toward the transition layer 20). The protrusions are in the shape of a water drop; the diameter of the protrusions is 2.5 mm and the height is 1.0 mm; the distance between two adjacent protrusions is 8 mm; the number of protrusions per unit area in the first protective layer 30 is 1.5x10 4 indivual.

[0046] The first thermal insulation layer 40 is made of basalt fiber reinforced silica aerogel felt, and the thickness of the first thermal insulation layer 40 is 5 mm; wherein the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:1, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.017 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 160 kg / m 3 The bulk density of the preform formed by basalt fiber is 80kg / m 3 , the density of silica aerogel is 80kg / m 3 .

[0047] The thickness of the second thermal insulation layer 50 is 5 mm. The second thermal insulation layer 50 adopts phase change material, which is composed of a phase change raw material and a matrix material. The phase change raw material is a microcapsule, and the average particle size of the microcapsule is 80 μm. The encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:30:5. The phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e., melamine formaldehyde resin) and the paraffin is 6:1. The matrix material is epoxy resin, and the mass ratio between epoxy resin (matrix material) and microcapsule (phase change raw material) is 1:8. The phase change temperature of the phase change material is 120°C, and the density is 1.3 g / cm 3 , phase change enthalpy is 260J / g.

[0048] The thickness of the second protective layer 60 is 0.1 mm. The second protective layer 60 is a flat and smooth metal titanium foil, which facilitates the installation of the second protective layer 60 .

[0049] Comparative Example 1:

[0050] A composite structure comprises a fireproof layer, a transition layer, a first protective layer, a first thermal insulation layer, a second thermal insulation layer and a second protective layer in sequence, wherein the thickness and material of the fireproof layer, the transition layer, the first thermal insulation layer, the second thermal insulation layer and the second protective layer are consistent with those in Example 2; the thickness of the first protective layer is 0.06 mm and the first protective layer is a flat and smooth metal titanium foil.

[0051] Comparative Example 2:

[0052] A composite structure comprises a fireproof layer, a transition layer, a first protective layer, a heat-insulating layer A and a second protective layer in sequence, wherein the thickness and material of the fireproof layer, the transition layer, the first protective layer and the second protective layer are consistent with those in Example 2; the heat-insulating layer A adopts basalt fiber reinforced silica aerogel felt, and the thickness of the heat-insulating layer A is 6 mm; wherein the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of the basalt fiber to the silica aerogel is 1:0.85, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.018 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 163.24 kg / m 3 The bulk density of the preform formed by basalt fiber is 88.24kg / m 3 The density of silica aerogel is 75kg / m 3 .

[0053] Comparative Example 3:

[0054] A composite structure comprises a fireproof layer, a transition layer, a first protective layer, a heat-insulating layer B and a second protective layer in sequence, wherein the thickness and materials of the fireproof layer, the transition layer, the first protective layer and the second protective layer are consistent with those in Example 2; the thickness of the heat-insulating layer B is 6 mm; the heat-insulating layer B adopts a phase change material, the phase change material is composited by a phase change raw material and a matrix material, the phase change raw material is a microcapsule, the average particle size of the microcapsule is 60 μm, wherein the encapsulating material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulating material is 10:25:3; the phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulating material (i.e., melamine formaldehyde resin) and the paraffin is 6:1; the matrix material is epoxy resin, and the mass ratio between the epoxy resin (matrix material) and the microcapsule (phase change raw material) is 1:6; the phase change temperature of the phase change material is 110°C, and the density is 1.2 g / cm 3 , phase change enthalpy is 240J / g.

[0055] Comparative Example 4:

[0056] A composite structure comprises a fireproof layer, a transition layer, a first protective layer, a first heat-insulating layer, a second heat-insulating layer and a second protective layer in sequence, wherein the thickness and material of the transition layer, the first protective layer, the first heat-insulating layer, the second heat-insulating layer and the second protective layer are consistent with those in Example 2; the thickness of the fireproof layer 10 is 0.8 mm, and the fireproof layer 10 adopts an intumescent fire-retardant coating, and the intumescent fire-retardant coating comprises a film-forming material, a flame retardant and a functional filler, wherein the mass ratio between the film-forming material, the flame retardant and the functional filler is 2.5: 8:2; the film-forming material is a high-elastic polyurethane polymer (wherein the high-elastic polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 6:5:3; the functional filler is composed of expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 35μm, and the melting point is not less than 1600℃), and the mass ratio between them is 3:5.

[0057] The composite structure samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were respectively fixed on the tooling of the inner cavity of the heating device. Three temperature sensors were arranged on the cold surface of the sample and the three temperature sensors were evenly distributed on the cold surface of the sample. When the ambient temperature was 23°C (the other test conditions were also the same) and the hot surface temperature was 800°C, the cold surface temperatures of the corresponding samples were obtained respectively. The test time was 300s. The test results are as follows:

[0058]

[0059] As shown in the table above: the use of the structural combination of the specific fireproof layer, transition layer, first protective layer, first thermal insulation layer, second thermal insulation layer, and second protective layer of the present application in combination with the specific material combination of the corresponding structural layer can effectively improve the fireproof and thermal insulation properties of the composite structure. Under the action of a long period of time (i.e., 300s) at a hot surface temperature of 800°C, the average temperature of the cold surface of the composite structure prepared by the present application is not greater than 60°C, which is significantly lower than that of the composite structures prepared in Comparative Examples 1 to 4; at the same time, the temperature difference of each temperature measuring point of the composite structure prepared by the present application is small, which proves that the structure of the present application can dissipate heat evenly and there is no temperature concentration point, while the temperature deviation of the temperature measuring point of the composite structure in Comparative Examples 1 to 4 is large, which also indirectly proves that the interlayer thermal insulation effect of the present application is good.

Claims

1. A fireproof and heat-insulating integrated composite structure, characterized in that: It includes a fireproof layer, a transition layer, a first protective layer, a first heat-insulating layer, a second heat-insulating layer and a second protective layer in sequence; wherein the fireproof layer adopts an intumescent fire-retardant coating, the transition layer adopts a primer, the first protective layer and the second protective layer adopt metal titanium foil, the first heat-insulating layer adopts aerogel felt, and the second heat-insulating layer adopts a phase change material; The transition layer uses epoxy primer, and the thickness of the transition layer is 40 to 60 μm; The thickness of the first protective layer is 0.03-0.1 mm; the first protective layer adopts a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure; the shape of the protrusions is any one of rice grains, pearls, and water drops; the diameter of the protrusions is 1-2.5 mm, and the height is 0.4-1.0 mm; the distance between two adjacent protrusions is 4-8 mm; the number of protrusions per unit area in the first protective layer is 1.5x10 4 ~6x10 4 indivual.

2. The fireproof and heat-insulating integrated composite structure according to claim 1, characterized in that: The thickness of the fireproof layer is 0.6-1.0 mm; the intumescent fireproof coating comprises a film-forming material, a flame retardant and a functional filler, wherein the mass ratio of the film-forming material, the flame retardant and the functional filler is 2-3:6-10:1-3.

3. The fireproof and heat-insulating integrated composite structure according to claim 2, characterized in that: The film-forming material is a high-elastic polyurethane polymer; the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 5-8:4-7:2-4; the functional filler is composed of nano-grade aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres, and the mass ratio between them is 5-10:2-5:3-8.

4. The fireproof and heat-insulating integrated composite structure according to claim 1, characterized in that: The first thermal insulation layer uses basalt fiber reinforced silica aerogel felt, and the thickness of the first thermal insulation layer is 2 to 5 mm; wherein the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.78 to 1, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.017 to 0.020 W / (m•K).

5. The fireproof and heat-insulating integrated composite structure according to claim 4, characterized in that: The thickness of the second thermal insulation layer is 2 to 5 mm; the phase change material is composed of a phase change raw material and a matrix material, the phase change raw material is a microcapsule, the particle size of the microcapsule is 10 to 100 μm, wherein the encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the phase change core of the microcapsule is paraffin; the matrix material is epoxy resin; the phase change temperature of the phase change material is 95 to 120°C, and the density is 1.0 to 1.3 g / cm 3 , phase change enthalpy value is 220~260J / g.

6. The fireproof and heat-insulating integrated composite structure according to claim 1, characterized in that: The thickness of the second protective layer is 0.03-0.1 mm, and the second protective layer is a flat and smooth metal titanium foil.

Citation Information

Patent Citations

  • Organic-inorganic composite nanometer heat-insulating fire-retardant coating and preparation method thereof

    CN104177965A

  • Fireproof cover and checking method thereof

    CN118149148A

  • Buffering and heat-insulating aerogel sheet

    CN214227007U